Light up your child's mind finding a unique pathway to happiness and success - Renzulli, Joseph S. 1936-; Reis, Sally M.; Thompson, Andrea (Little, Brown, 2009)
Based on the renowned Renzulli Method, which has been adopted in schools all over the country, "Light Up Your Child's Mind" presents a practical program to help children fire up a love of learning to last a lifetime.
Includes bibliographical references and index
Keywords: Erziehung; Gifted children -- Education; Gifted children; Child rearing; Unterricht; Schüler; Hochbegabung